Analisis Komparatif Laporan Keuangan Syariah Dan Non Syariah: Tinjauan Literatur Menuju Pasar Keuangan Yang Lebih Etis Dan Berkelanjutan - Nisrina Dian Trisya; Ria Ariyani; Nia Ira Syahara; Silvi Moli Lutfhia; Kharisma Khoirun Nisa; Ersi Sisdianto (Jurnal Riset Akuntansi, 2024)
Comparative analysis between sharia and non-sharia financial reports has become an increasingly relevant topic in the context of continuously developing global financial markets. In this study, we evaluate the differences in approaches, principles, and practices underlying these two types of financial reports. The results of the analysis highlight the implications of these differences in financial practices, economic growth, and financial market inclusivity. The discussion also highlighted the potential for collaboration between the two types of finance to produce innovation and best practices in financial and investment management.